Chronic Plaque Psoriasis and Metabolic Syndrome - Abbas, Mohammed Y. (AL-Kindy College Medical Journal, 2013)
AbstractBackground:Psoriasis is an inflammatorydiseasewhichcan be associated with otherdiseases, which may have amajor impact onpatientslife. Psoriasis has also been reported tobe associated with metabolic disorders.Metabolic syndrome(MS)isa combination ofmedicaldisorders that, when occurring together,increasesthe risk of development ofcardiovasculardiseasesanddiabetes.It affectsone in five people in the United States andtheprevalence increases with age. Some studieshave showntheprevalencein the USA to be anestimated 25% of the population.Objective:To investigate the prevalence ofmetabolic syndrome in patients with psoriasis.Methods: We performed a hospital-based case-